(untitled) (Revista científica Olimpia, 2020)
The attention to the biggest adults belongs one of the main objectives from the professor of Physical Culture when promoting the maintenance of the health and the biggest adult’s good physical and mental operation. For the realization of this investigation a sample of 30 adults was chosen bigger than the community Jesús Menendez, in the Municipality of Tree, County of Granma specifically with those that consume alcoholic drinks. The general objective is guided to: to apply recreational physical activities for the alcoholic bigger adults of the community Jesús Menendez, to achieve a decrease of their consumption. The results obtained through the diagnosis and the characterization to the biggest adults that consume drinks alcoholics demonstrate the necessity to carry out these activities to improve their quality of life, to achieve the decrease of their consumption and a concientización starting from the damages that it causes to the organism and in their behavior in the society.